2024
DOI: 10.1038/s43247-024-01304-y
|View full text |Cite
|
Sign up to set email alerts
|

The complex composition of organic aerosols emitted during burning varies between Arctic and boreal peat

Eric Schneider,
Christopher P. Rüger,
Martha L. Chacón-Patiño
et al.

Abstract: Peatlands in the northern hemisphere are a major carbon storage but face an increased risk of wildfires due to climate change leading to large-scale smoldering fires in boreal and Arctic peatlands. Smoldering fires release organic carbon rich particulate matter, which influences the earth’s radiative balance and can cause adverse health effects for humans. Here we characterize the molecular composition of biomass burning particulate matter generated by laboratory burning experiments of peat by electrospray ion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 95 publications
0
0
0
Order By: Relevance
“…Additionally, the ionization by APPI is very sensitive for sulfur-containing species, which may result in an overrepresentation of these species . The herein discussed results are in line with our previous study that revealed an unusually high abundance of sulfur-containing species (CHOS, CHNOS) in the polar fraction of the same peat combustion emission extracts …”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…Additionally, the ionization by APPI is very sensitive for sulfur-containing species, which may result in an overrepresentation of these species . The herein discussed results are in line with our previous study that revealed an unusually high abundance of sulfur-containing species (CHOS, CHNOS) in the polar fraction of the same peat combustion emission extracts …”
Section: Resultssupporting
confidence: 92%
“…However, in general, all four peat combustion extracts are vastly similar, regarding both the detected elemental compositions (70–87% common compounds, Figure S1) as well as their intensity distribution in the mass spectra (Figure S2), even though APPI is reported to be less prone to matrix effects . This result contrasts with observations made for the polar organic fraction of these aerosol extracts investigated in a previous study by ESI 21 T FT-ICR MS that revealed distinct differences between the boreal and the Arctic peat-burning aerosols in all compound classes . With regard to Figure , the CHO class is the most abundant compound class (approximately 50–54% int.)…”
Section: Resultscontrasting
confidence: 71%
See 3 more Smart Citations